Stability Evaluation on Surrounding Rocks of Underground Powerhouse Based on Microseismic Monitoring - Feng Dai; Biao Li; Nuwen Xu; Yongguo Zhu; Peiwei Xiao (Shock and Vibration)
To study the stability of underground powerhouse at Houziyan hydropower station during excavation, a microseismic monitoring system is adopted. Based on the space-time distribution characteristics of microseismic events during excavation of the main powerhouse, the correlation between microseismic events and blasting construction is established; and the microseismic clustering areas of the underground powerhouse are identified and delineated. The FLAC3D code is used to simulate the deformation of main powerhouse. The simulated deformation characteristics are consistent with that recorded by microseismic monitoring. Finally, the correlation between the macroscopic deformation of surrounding rock mass and microseismic activities is also revealed. The results show that multiple faults between 1# and 3# bus tunnels are activated during excavation of floors V and VI of the main powerhouse. The comprehensive method combining microseismic monitoring with numerical simulation as well as routine monitoring can provide an effective way to evaluate the surrounding rock mass stability of underground caverns.